Haematological parameters change in Gallus gallus domesticus infected with cestode parasite. - Aade, U P; Wankhede, H J; Kaldate, K D (International Multidisciplinary Research Journal, 2012)
The study deals with the haematological parameters in Gallus gallus domesticus (Linnaeus, 1758) which is naturally infected with cesode parasites. Inspite of the fact that the haematological value of birds (Gallus gallus domesticus) are of clinical significant rates than commercial importance.Â  The total erythrocytes and leukocyte count, haemoglobin and haematocrit value, mean corpuscular volume and differential leukocyte count were determined. There is a significant decrease in erythrocytes count and haemoglobin concentration, haematocrit value. While the total leukocyte count was increase in the infected as compare to the normal Gallus gallus domesticus. The obtained result collectivities indicate the change in heamatology of Gallus gallus domesticus infected with cestode parasites. The haematological parameters of the infected bird Gallus gallus domesticus shows high infection cause macrocytic anemia, lymphocytosis due to deficiency of related factors.